2022
DOI: 10.1126/scitranslmed.abj4772
|View full text |Cite|
|
Sign up to set email alerts
|

Modeling injury and repair in kidney organoids reveals that homologous recombination governs tubular intrinsic repair

Abstract: Kidneys have the capacity for intrinsic repair, preserving kidney architecture with return to a basal state after tubular injury. When injury is overwhelming or repetitive, however, that capacity is exceeded and incomplete repair results in fibrotic tissue replacing normal kidney parenchyma. Loss of nephrons correlates with reduced kidney function, which defines chronic kidney disease (CKD) and confers substantial morbidity and mortality to the worldwide population. Despite the identification of pathways invol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
56
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 63 publications
(59 citation statements)
references
References 81 publications
3
56
0
Order By: Relevance
“…Residual Rh123 uptake in the presence of OCTi inhibitors suggests the presence of alternate basolateral uptake pathways for this molecule. Nonetheless, our results show that organoids express OCT2, consistent with previous reports that organoids were able to recapitulate kidney injury induced by cisplatin, a substrate of OCT2 (Morizane et al, 2015;Digby et al, 2020;Gupta et al, 2022).…”
Section: Discussion and Outlooksupporting
confidence: 92%
See 1 more Smart Citation
“…Residual Rh123 uptake in the presence of OCTi inhibitors suggests the presence of alternate basolateral uptake pathways for this molecule. Nonetheless, our results show that organoids express OCT2, consistent with previous reports that organoids were able to recapitulate kidney injury induced by cisplatin, a substrate of OCT2 (Morizane et al, 2015;Digby et al, 2020;Gupta et al, 2022).…”
Section: Discussion and Outlooksupporting
confidence: 92%
“…Bulk RNA-seq analysis in our recent study suggests that kidney organoids mature during 7 weeks of differentiation in culture (Gupta et al, 2022). To evaluate the functional maturation of tubular transport, we compared the Rh123 transport activities in kidney organoids longitudinally during this period of differentiation, and specifically on days 21 (d21), 35 (d35), and 49 (d49).…”
Section: Live Functional Assay Elucidates Functional Maturation Of Ki...mentioning
confidence: 99%
“…Human kidney organoids made from induced pluripotent stem (iPS) cells have been used to model human development 46 , and to model some human kidney pathologies from patient-derived iPS cells 47 – 49 and from cells engineered to have genetic defects 48 . They have also been used to investigate critical pathways in renal repair 50 , and to model pathways of drug-induced nephrotoxicity 51 and to screen for and report nephrotoxicity fluorescently 52 . It is important to note, though, that there are differences between human and mouse development 53 and caution should be used in extrapolating from one to the other.…”
Section: Discussionmentioning
confidence: 99%
“…Tanigawa et al established organoids created from NPHS1 missense mutations, where the podocyte foot process showed impaired slit diaphragm formation ( Tanigawa et al, 2018 ). Furthermore, Gupta et al identified the novel intrinsic repair mechanism using kidney organoids ( Gupta et al, 2022 ). By using single-nuclear RNA sequencing analysis of kidney organoids after cisplatin exposure, they identified the transient up-regulation of Fanconi anemia complementation group D2 ( FANCD2 ) and RAD51 recombinase ( RAD51 ) during intrinsic repair, and the down-regulation of these genes in incomplete repair.…”
Section: De Novo Kidney Fabricationmentioning
confidence: 99%